Large‐scale variation in wave attenuation of oyster reef living shorelines and the influence of inundation duration. Issue 6 (29th June 2021) - Morris, Rebecca L.; La Peyre, Megan K.; Webb, Bret M.; Marshall, Danielle A.; Bilkovic, Donna M.; Cebrian, Just; McClenachan, Giovanna; Kibler, Kelly M.; Walters, Linda J.; Bushek, David; Sparks, Eric L.; Temple, Nigel A.; et al.
Abstract: One of the paramount goals of oyster reef living shorelines is to achieve sustained and adaptive coastal protection, which requires meeting ecological (i.e., develop a self‐sustaining oyster population) and engineering (i.e., provide coastal defense) targets. In a large‐scale comparison along the Atlantic and Gulf coasts of the United States, the efficacy of various designs of oyster reef living shorelines at providing wave attenuation was evaluated accounting for the ecological limitations of oysters with regard to inundation duration. A critical threshold for intertidal oyster reef establishment is 50% inundation duration. Living shorelines that spent less than one‐half of the time (<50%) inundated were not considered suitable habitat for oysters, however, were effective at wave attenuation (68% reduction in wave height). Reefs that experienced >50% inundation were considered suitable habitat for oysters, but wave attenuation was similar to controls (no reef; 5% reduction in wave height). Many of the oyster reef living shoreline approaches therefore failed to optimize the ecological and engineering goals. In both inundation regimes, wave transmission decreased with an increasing freeboard (difference between reef crest elevation and water level), supporting its importance in the wave attenuation capacity of oyster reef living shorelines. However, given that the reef crest elevation (and thus freeboard) should be determined by the inundation duration requirements of oysters, research needs to be refocused on understanding the implications of other reef parameters (e.g., width) for optimizing wave attenuation. A broader understanding of the reef characteristics and seascape contexts that result in effective coastal defense by oyster reefs is needed to inform appropriate design and implementation of oyster‐based living shorelines globally.